2021
DOI: 10.1155/2021/6636947
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis Value of a Novel Model with 5 Circulating miRNAs for Liver Fibrosis in Patients with Chronic Hepatitis B

Abstract: Background and Aim. miRNAs play an important role in the development of human fibrosis. However, miRNA expression profiles during different stages of chronic hepatitis B (CHB) are not well defined. In this study, we aimed to further validate the features of 5 miRNA candidates from our previous study during different fibrotic stages and the value of diagnosis for liver fibrosis. Methods. Differential expression of five selected miRNAs (hsa-mir-1225-3p, hsa-mir-1238, hsa-miR-3162-3P, hsa-miR-4721, and hsa-miR-H7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Beside miR-320, there are many other miRNAs that were strongly deregulated in the patient populations. Of the most upregulated miRNAs, miR-374a-3p and miR-15a-3p are involved in acute kidney and neuroinflammation, respectively, whereas mir-4721 was proposed as one of the miRNA molecular diagnostic markers for liver fibrosis in patients with chronic hepatitis B [ 36 , 37 , 38 ]. Of the most downregulated miRNAs, miR-4747-3p was found upregulated in Alzheimer’s Disease and hsa-miR-4429 was suggested as a potential diagnostic biomarker for biliary atresia [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beside miR-320, there are many other miRNAs that were strongly deregulated in the patient populations. Of the most upregulated miRNAs, miR-374a-3p and miR-15a-3p are involved in acute kidney and neuroinflammation, respectively, whereas mir-4721 was proposed as one of the miRNA molecular diagnostic markers for liver fibrosis in patients with chronic hepatitis B [ 36 , 37 , 38 ]. Of the most downregulated miRNAs, miR-4747-3p was found upregulated in Alzheimer’s Disease and hsa-miR-4429 was suggested as a potential diagnostic biomarker for biliary atresia [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-150-5p expression was generally positively correlated with fibrosis severity in rats with carbon tetrachloride-induced liver fibrosis ( Chen et al, 2020b ). On the other hand, in chronic HBV-infected patients, miR-3162-3p expression was higher in the serum of individuals with significant liver fibrosis than those with nonsignificant liver fibrosis ( Zhang et al, 2021 ). In addition to these aforementioned miRNAs and somewhat elusive information, 11 out of 13 miRNAs were shown to be involved in liver cirrhosis for the first time with bioinformatics analysis, and the expression of 7 miRNAs was proved to undergo significant changes in LX2 cells challenged with TGF- β 1 in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Azar et al [ 65 ] constructed a miRNA regulatory network using bioinformatics tools and identified five upregulated miRNAs (miR-21-5p, miR-222-3p, miR-221-3p, miR-181b-5p, and miR-17-5p) that targeted tissue inhibitor of metalloproteinase 3 in activated HSCs, and these results have been verified in a mouse model of liver fibrosis. Zhang et al [ 66 ] performed a logistic regression analysis to show that miR-1225-3p, miR-1238, miR-3162-3p, miR-4721, and miR-H7 could distinguish, with high sensitivity and specificity, nonsignificant fibrosis from significant fibrosis in chronic hepatitis B (CHB) patients. Some researchers screened miRNAs in serum from HCV-related liver fibrosis patients and found that miR-484 was significantly downregulated in advanced liver fibrosis compared to early liver fibrosis and liver cancer[ 67 ], which indicates that miR-484 may be used as a biomarker for staging liver fibrosis in patients with HCV.…”
Section: Potential Application Of Ncrnas In the Diagnosis Of Liver Fi...mentioning
confidence: 99%